Edukasi Strategi Trading dalam Meningkatkan Pemahaman Literasi Keuangan Masyarakat - Sihite, Grace Thereskova Da Silvi; Rini, Hesty Prima (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Commodity futures trading, particularly gold (XAUUSD), offers significant profit potential with high risks, especially for novice traders who lack an understanding of appropriate trading strategies to minimize potential losses and market uncertainties. This community service activity aims to enhance public financial literacy through direct trading strategy education. The method used is interactive training based on direct experience (experiential learning) with real-time practice using the Metatrader 5 platform, covering technical analysis and the application of stop loss and take profit to minimize risks. The activity results show a significant improvement in the understanding of trading strategies. This program proves that the hands-on learning approach is effective in shaping more measured traders and protecting them from losses due to a lack of knowledge. Thus, structured education like this is essential to create a sustainable trading ecosystem in Indonesia.